2019
DOI: 10.1101/638528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Staphylococcus aureus infects osteoclasts and replicates intracellularly

Abstract: Osteomyelitis (OM), or inflammation of bone tissue, occurs most frequently as a result of bacterial infection and severely perturbs bone structure. The majority of OM is caused by Staphylococcus aureus, and even with proper treatment, OM has a high rate of recurrence and chronicity. While S. aureus has been shown to infect osteoblasts, persist intracellularly, and promote the release of pro-osteoclastogenic cytokines, it remains unclear whether osteoclasts (OCs) are also a target of intracellular infection. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Third, the infecting organisms adapt. Not only do they mutate into resistant forms and persist in biofilm slime, but recent work has demonstrated that Staphylococcus Aureus, at least, can hide and multiply in healthy appearing bone and intracellularly in osteocytes, osteoblasts and osteoclasts (Krauss et al 2019). The demands that these factors place on antibiotics have rendered our historical reference, the Minimal Inhibitory Concentration (MIC), irrelevant in these patients and have led to new acronyms, the Minimal Biofilm Inhibitory Concentration (MBIC), and the Minimal Biofilm-Eradication Concentration (MBEC), that are attempting to give partial insight into local levels needed for successful treatment (Bayramov and Neff 2017).…”
Section: Retrograde Flow-screw Calcaneal Intraosseousmentioning
confidence: 99%
“…Third, the infecting organisms adapt. Not only do they mutate into resistant forms and persist in biofilm slime, but recent work has demonstrated that Staphylococcus Aureus, at least, can hide and multiply in healthy appearing bone and intracellularly in osteocytes, osteoblasts and osteoclasts (Krauss et al 2019). The demands that these factors place on antibiotics have rendered our historical reference, the Minimal Inhibitory Concentration (MIC), irrelevant in these patients and have led to new acronyms, the Minimal Biofilm Inhibitory Concentration (MBIC), and the Minimal Biofilm-Eradication Concentration (MBEC), that are attempting to give partial insight into local levels needed for successful treatment (Bayramov and Neff 2017).…”
Section: Retrograde Flow-screw Calcaneal Intraosseousmentioning
confidence: 99%
“…Moreover, a key characteristic of osteomyelitis is formation of a biofilm, which confers a therapeutically relevant level of intrinsic resistance to all antibiotics at both an aggregate and cellular level [7][8][9]. S. aureus can also invade, survive, and even replicate inside osteoblasts and osteoclasts, thus providing further protection from antibiotics and host defenses [10][11][12][13]. As a result, the effective treatment of osteomyelitis requires a multidisciplinary approach that includes long-term systemic antibiotic therapy and surgical debridement, often accompanied by some form of local, matrix-based antibiotic delivery directly to the site of infection [5,6,14,15].…”
Section: Introductionmentioning
confidence: 99%